2009
DOI: 10.1002/da.20436
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenon of declining anxiety sensitivity scores: a controlled investigation

Abstract: Several potential explanations for these findings are reviewed and implications for research study designs are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
4
20
1
1
Order By: Relevance
“…The low-exposure group completed the ASI-R twice, at baseline and at the last administration. However, to protect against non-specific effects associated with researcher contact, participants in the low-exposure group returned to the laboratory two times during the 2-week period to complete a non-AS questionnaire (a measure of self-esteem) which does not decline across time or affect AS scores (Broman-Fulks et al 2009). In the high-exposure condition, the second administration of the ASI-R occurred the day following the baseline administration.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The low-exposure group completed the ASI-R twice, at baseline and at the last administration. However, to protect against non-specific effects associated with researcher contact, participants in the low-exposure group returned to the laboratory two times during the 2-week period to complete a non-AS questionnaire (a measure of self-esteem) which does not decline across time or affect AS scores (Broman-Fulks et al 2009). In the high-exposure condition, the second administration of the ASI-R occurred the day following the baseline administration.…”
Section: Methodsmentioning
confidence: 99%
“…Results of a study specifically designed to evaluate regression to the mean and the inclusion of anxiety-related information revealed that the declines in AS scores could not be attributed to regression to the mean or exposure to information about anxiety in general (Broman-Fulks et al 2009). Specifically, both individuals with low and high AS scores (ASI-R scores in the bottom and top quartiles, respectively) showed similar and significant declines in AS scores from the first to the second administration of the ASI-R conducted the same day, indicating that declines in AS scores are not due simply to regression to the mean.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AD'nin zaman içinde değişebileceği iddia edilmiş ise de (Schmidt ve ark. 2000, Broman-Fulks ve ark. 2009); yayınlanan meta analizlere ve ikiz çalışmalarına göre bir kişilik özelliği olarak kavramsallaştırılması daha uygundur (Taylor ve ark.…”
Section: Introductionunclassified